Closing the Scottian shortfall in the Brazilian Caatinga seasonally dry forests: conservation status of endemic bat-pollinated angiosperms and their main threats - Hadassa Carolinny Soares de Oliveira; Márlon Carlos da Silva Cintra; Sinzinando Albuquerque-Lima; Swanni T. Alvarado; Edlley Max Pessoa (Plant Ecology and Evolution)
Background and aims – Bats are the third most important animal pollinators in the Brazilian Caatinga seasonally dry forest, but little is known about the conservation status of the chiropterophilous plant species in this domain, and their main threats. The Scottian shortfall relates to deficits in assessments of IUCN conservation statuses. We aimed to evaluate the current conservation status of chiropterophilous species in the Caatinga, investigate the main changes in land use and land cover in the last years and their impacts on conservation of these species. Material and methods – We compiled a dataset and evaluated the extinction risk of 16 species following the IUCN Red List categories and criteria using the geographic range criterion. Analyses of reductions of natural vegetation were carried out using data from the project MapBiomas. Key results – Our results show that approximately 80% of the assessed species saw their conditions worsen in the last years. We verified that Dyckia viridiflora and Ipomoea vespertilia are categorized as Endangered and Stigmatodon limae is considered Vulnerable. The main sources of disturbances impacting these species according to land use are pastures and mosaics of land uses, but we highlight that urbanization is the second or third most important threat for all species. The three main threats affected the species differently. Although half of the species is assessed as Least Concern, all species had their suitable areas impacted by human activities.